2011
DOI: 10.1111/j.1349-7006.2011.01858.x
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐negative breast cancer: Histological subtypes and immunohistochemical and clinicopathological features

Abstract: To reveal heterogeneous properties of triple-negative (TN) breast cancers (estrogen receptor negative, progesterone receptor negative and HER2 negative) and to clarify whether the developmental pathways to TN breast cancer are single or multiple, we conducted clinicopathological and immunohistochemical studies on TN breast cancers, with special reference to comparison of the invasive component (iIC) and the ductal component (dcIC) of invasive TN breast cancer and pure TN ductal carcinoma in situ (TNDCIS). Tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
2
20
2
Order By: Relevance
“…Tumors with an Allred score ‡ 3 and nuclear staining of more than 10% of the tumor cells were classified as ER-positive or PR-positive (Ishikawa et al, 2011). P53 was defined as positive when more than 25% (median value) of the tumor cells were positive for nuclear staining.…”
Section: Determination Of Clinicopathological Featuresmentioning
confidence: 99%
“…Tumors with an Allred score ‡ 3 and nuclear staining of more than 10% of the tumor cells were classified as ER-positive or PR-positive (Ishikawa et al, 2011). P53 was defined as positive when more than 25% (median value) of the tumor cells were positive for nuclear staining.…”
Section: Determination Of Clinicopathological Featuresmentioning
confidence: 99%
“…They frequently show features of ductal invasive carcinomas [12] although metaplastic, medullary and apocrine features are also found [9, 13]. Moreover, TNBCs may present themselves as adenoid cystic lesions, histiocytoid carcinomas and even as invasive lobular carcinomas [13].…”
Section: Pathological and Molecular Characterization Of Triple Negatimentioning
confidence: 99%
“…Few studies have described the existence of pure ductal carcinoma in situ with the basal phenotype, with Zhou et al reporting a doubled risk for local recurrence and invasion in basal-like in situ ductal carcinoma 17–21. It was suggested that an in situ component was less frequently observed in triple negative invasive breast carcinoma owing to rapid disease progression 14. More recently, Clark et al 22 documented triple negative and basal-like rates of ductal carcinoma in situ as 7.5% and 4.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%